Regenerative and innovative processes in the urban and peri-urban area of the city of Rome - Alessandra Cornice; Alessandra Innamorati (Techne)
Rome stands out for a fragility that stems from the disordered interpenetration of its rural soul with its urban agglomeration. The relationship between city and suburbs still appears complicated today and reverberates on the degree of social cohesion of its inhabitants. Bottom-up experimentation projects are being grafted into the extended area of the capital, reviving disused public property, abandoned land, to eliminate degradation especially in fragile contexts, developing regenerative processes of active citizenship. The purpose of the paper is to underline innovative experiences, in the urban and peri-urban area of Rome, pointing out their actions aimed at sharing common values, developing territorial welfare and protecting the environment.